Examining the Behavior in Public Good Games: An Application of Prisoner’s Dilemma - Khan, Zarlasht; Maud, Hadiya; Zubair, Mariam; Salman, Verda; Nazuk, Ayesha (Pakistan Business Review, 2022)
Standard belief in economic theory asserts that effective public good provision will always be hindered by the presence of free-riders. Yet in contradiction to this, many collective goods have managed to be effectively provided by large bodies of people working together. This begs the question: how prevalent is free-ridership in reality and how well does theory translate into practice? We have tested this theory by subjecting participants to experimental conditions where the impacts of social pressure have been observed via the formation of groups of four. Results have shown that, though individuals are likely to contribute in our treatment condition; even in the absence of social pressure, individuals will willingly donate around 40% of their endowments. This has allowed us to conclude that, in our experiment, the free rider hypothesis is not supported.
Keywords: Free-rider; public good provision; social pressure; groups